Bandwidth Quota Configuration For Internet Access At Pematangsiantar Mayor's Office: Bandwidth Quota Configuration For Internet Access At Pematangsiantar Mayor's Office - Daniel Saputra Sitorus; Sumarno Sumarno; Zulaini Masruro Nasution; Indra Gunawan; Hendrik Qurniawan (Jurnal Mantik, 2020)
Decreasing network performance Along with increasing network users. The way that can be done to reduce network performance degradation is by doing bandwidth management. Bandwidth management is very important in determining the bandwidth allocation that will be given to users to exceed the existing bandwidth allocation in the network. MikroTik Routerboard is one type of proxy that has a special operating system, namely the MikroTik OS Router has QoS which is used for full bandwidth usage licenses. This study provides bandwidth sharing with the Queue Tree method)